Återtagning av små fastvingsdrönare i sjöräddningsmiljö - Bergman, Andreas (My University)
This thesis work was conducted in collaboration with Sjöräddningssällskapet (SSRS), which utilizes unmanned aerial vehicles (UAVs) to support maritime rescue operations. In coastal environments with small landing space and variable wind conditions, conventional landing methods for fixed-wing UAVs are not always suitable. The objective of this project was therefore to develop a conceptual system for safe mid-air capture and retrieval of a small fixed-wing UAV adapted to SSRS operational requirements. The work followed a structured product development process. After establishing system requirements and performing a functional analysis, solution principles were generated using a morphological matrix. Partial solutions and overall concepts were reduced through a systematic elimination process, excluding technically unsuitable or impractical alternatives. The remaining concepts were further analysed with respect to energy absorption, feasibility, and operational applicability. The final concept consists of a portable, modular capture system based on mechanical energy absorption through a tensioned line between two interconnected units. The system is dimensioned according to the UAV’s kinetic energy at approach, enabling a compact design compared to large-scale commercial systems. Analytical calculations indicate that the concept is feasible at a conceptual level and capable of handling the expected loads. The study demonstrates that an established capture principle can be scaled and adapted to maritime rescue applications through systematic concept development. Future work should include prototype development and experimental validation under realistic operating conditions.